"Enemy Territory": Immigration Enforcement in the US-Mexico Borderlands. (September 2014) - Ewing, Walter A.
For the last two decades, the guiding strategy of immigration enforcement along the US-Mexico border has been "prevention through deterrence, " or stopping unauthorized immigrants from entering the country rather than apprehending those who have already crossed the border. "Prevention through deterrence" has entailed a massive concentration of enforcement personnel and resources along the border and at ports of entry. It has also led to the detention and removal of increasing numbers of unauthorized immigrants and far greater use of "expedited removal." As gauged by the doubling in size of the unauthorized immigrant population over the same period, "prevention through deterrence" has not been a successful enforcement strategy. Moreover, it has funneled more migrants to their death in the deserts and mountains of the southwest as they (and smugglers) resort to increasingly dangerous routes to evade border enforcement. In addition, there has been public concern over ethnic profiling and the use of extraordinary authority by Border Patrol agents to conduct arbitrary searches within 100 miles of the border. Despite these problems, the federal government continues to spend billions of dollars each year on the "prevention through deterrence" strategy. A first step in overcoming the deficiencies of this border enforcement strategy is to strengthen accountability within the Border Patrol, so that allegations of excessive force and abuse are investigated and adjudicated promptly and appropriately. The culture of the Border Patrol must be transformed to foster respect for rights. More broadly, the mission of the Border Patrol should be to capture dangerous individuals and to disrupt the operations of the transnational criminal organizations that traffic people, drugs, guns, and money. In addition, providing more pathways to legal entry through immigration reform would enhance border security by attenuating the flow of unauthorized immigrants within which dangerous criminals or terrorists can hide. Finally, the US government should pursue economic policies to promote development in Mexico and Central American countries in order to address the underlying causes of migration.